SISTEM INFORMASI GEOGRAFIS FASILITAS KESEHATAN BPJS DI KOTA PALANGKA RAYA BERBASIS ANDROID - licantik, licantik; Nova Noor Kamala Sari (Universitas Palangka Raya, 2020)
Today the development of technology has been increasing rapidly as well as the use of android smartphones in the field of information systems. It is familiar among the public because it can help in getting the information in a fast and accurate way particularly in an emergency situation. Human needs for information, one of them is information of health facilities in collaboration with Badan Penyelenggara Jaminan Sosial (BPJS) or Agency of Social Security. The purpose of this study is to produce an Android-based application that can facilitate the public in getting information of health facilities in collaboration with BPJS in Palangkaraya. The method applied in the system development in this study is the Waterfall model which consists of five stages, namely, need analysis, system of design, program code writing, program testing, and program implementation. In addition, in creating process, the program uses Android studio software with java programming language and XAMPP connection database, up to UML (Unifield Modeling Language) to depict the system to be made. From this study, the test result shows that the functionality of the BPJS health facility Geographic Information System (GIS) in Palangkaraya City is going well and is in accordance with its function. This android-based application system can display online maps of BPJS health facility locations as well as detailed information from BPJS health facilities in Palangkaraya